The learning primacy hypothesis of dopamine: reconsidering dopamine’s dual functions - Long, Charltien; Masmanidis, Sotiris C. (Frontiers in Cellular Neuroscience, 2025)
The dopaminergic modulation of striatal circuit function remains intensely studied and debated. Nevertheless, a prevalent view is that striatal dopamine serves important roles in both reinforcement learning and the performance of movements, two highly distinct processes. But this dichotomy has led to a longstanding problem of how to interpret the functional consequences of a particular dopaminergic signal—is it to learn or to move? In order to explore this ambiguity and approach a possible resolution, this review examines the key evidence for dopamine’s role in learning and movement. As part of that discussion, we consider a recent body of evidence that views the common dichotomous perspective through a more nuanced lens, by suggesting a comparatively limited dopaminergic contribution to movement. This concept, which we refer to as the learning primacy hypothesis, offers a unified conceptual framework for understanding dopaminergic function.